Corpus of Academic Learner English (CALE): A new corpus at the intersection of corpus linguistics and English for academic purposes - Ayşe Şahin Kızıl (Literacy Trek, 2020)
Offering insights into varieties of English language, corpus compilation practices and corpus-based research have great potential to enhance the field of English for Academic Purposes (EAP). Among different types of corpora, learner corpora seem particularly promising as they document different aspects of learner language that might otherwise go unnoticed. Acknowledgement of potential contribution of learner corpora to EAP has led up to scientific efforts to compile learner corpora for academic purposes. This paper is the description of such an effort. The aim of this study is twofold: first, to highlight the possible contributions of language corpora to EAP; and second, to introduce the Turkish subcomponent of the Corpus of Academic Learner English (CALE-TR), as a new English for Academic Purposes corpus, currently being compiled for the investigation of learner academic writing.